Traumatic testis dislocation: a case report and review of the literature - (:unkn) unknown (MEDCOM LTD, 2012)
Dislocation of testis is a rare and underreported condition, commonly associated with delayed diagnosis and treatment in pelvic injuries. Delayed treatment may cause infertility due to elevated temperature exposure leading to a reduced sperm production. It is imperative to look for this entity during the secondary survey in the management of a polytrauma patient. We encountered dislocation of testis in a 26-year-old male motorcyclist involving in a road traffic crash. He complained of pelvic pain. A tender mass was felt in the left groin during physical examination. Abdominal computed tomography scan revealed a dislocated left testis. Closed reduction was performed and the patient recovered without any complications. (Hong Kong j. emerg.med. 2012;19:295-297)
Keywords: Computed tomography; traffic accidents; ultrasonagraphy doppler; wounds and injuries; BLUNT SCROTAL TRAUMA; TESTICULAR DISLOCATION; DIAGNOSIS